Geometric Power Lindley Poisson Distribution: Properties and Applications - Mahmoud M. Mansour (Journal of Statistical Theory and Applications (JSTA), 2016)
In this Paper, a new four-parameter distribution motivated mainly by dealing with series-parallel system is introduced. Moments, conditional moments and moment generating function of the new distribution including are presented. Estimation of its parameters is studied. characterization of the new model is introduced.